The impact of the increased speed of trains on the losses associated with the wear gauge infrastructure - Korzhenevych, I. P.; Kurhan, M. B.; Barash, Yu. S. (Science and Transport Progress, 2008)
An influence of the increase of speed of train movement on the expenditures related to wear of rail infrastructure is considered.